Reason and faith - Fiske, A. S. (The Neale company, 1900)
The atheistic argument from the existence of evil.--The theistic solution of the problem of evil in the world.--The rational ground of Christian faith.--The miracle reasonable.--The justification of the unjust.--The wonder of the word.--Why I beieve in God.--A conclusion of sound reason.--The unity of Christ's people.--The way of certitude.--Reason and faith.